Analisis Arus Dana Usaha Ternak Sapi Perah dengan Modal Pinjaman Kredit (Kasus di Cisarua, Bogor, Jawa Barat) - Rosmijati Sajuti; Pantjar Simatupang; Erizal Jamal; Chairul Muslim (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1993)
The government policy on dairy development has been primarily focused on development of small scale dairy farming. One of the development instruments is the dairy credit scheme. Each recipient of these credit is provided with 1-2 dairy cows. This study is primarily intended to evaluate the economic viability of the credit scheme using a cash flow analysis in 7 years period. The study was conducted in Cisarua, Bogor in April-May 1992. The analysis shows that the surplus obtained from a dairy farm supported by one dairy cow credit is only sufficient to meet 33.7 percent of the farmers's family basic need. This indicates that a credit scheme with only one dairy cow is not sufficient to support a sustainable primary family dairy farming. The minimum credit package to support a sustainable dairy farming would be 3 cows for a family labor-using dairy farming and 5 cows for a hired labor-using dairy farming.